New insight into avian malaria vectors in New Zealand - Schoener ER; Tompkins DM; Howe L; Castro IC (BioMed Central Ltd, 2024)
BACKGROUND: Mosquitoes (Culicidae) are vectors for most malaria parasites of the Plasmodium species and are required for Plasmodium spp. to complete their life cycle. Despite having 16 species of mosquitoes and the detection of many Plasmodium species in birds, little is known about the role of different mosquito species in the avian malaria life cycle in New Zealand. METHODS: In this study, we used nested polymerase chain reaction (PCR) and real-time PCR to determine Plasmodium spp. prevalence and diversity of mitochondrial cytochrome b gene sequences in wild-caught mosquitoes sampled across ten sites on the North Island of New Zealand during 2012-2014. The mosquitoes were pooled by species and location collected, and the thorax and abdomens were examined separately for Plasmodium spp. DNA. Akaike information criterion (AIC) modeling was used to test whether location, year of sampling, and mosquito species were significant predictors of minimum infection rates (MIR). RESULTS: We collected 788 unengorged mosquitoes of six species, both native and introduced. The most frequently caught mosquito species were the introduced Aedes notoscriptus and the native Culex pervigilans. Plasmodium sp DNA was detected in 37% of matched thorax and abdomen pools. When considered separately, 33% of abdomen and 23% of thorax pools tested positive by nested PCR. The MIR of the positive thorax pools from introduced mosquito species was 1.79% for Ae. notoscriptus and 0% for Cx. quinquefasciatus, while the MIR for the positive thorax pools of native mosquito species was 4.9% for Cx. pervigilans and 0% for Opifex fuscus. For the overall MIR, site and mosquito species were significant predictors of Plasmodium overall MIR. Aedes notoscriptus and Cx. pervigilans were positive for malaria DNA in the thorax samples, indicating that they may play a role as avian malaria vectors. Four different Plasmodium lineages (SYAT05, LINN1, GRW6, and a new lineage of P (Haemamoeba) sp. AENOT11) were identified in the pooled samples. CONCLUSIONS: This is the first detection of avian Plasmodium DNA extracted from thoraxes of native Culex and introduced Aedes mosquito species in New Zealand and therefore the first study providing an indication of potential vectors in this country.
Keywords: Aedes; Culex; Plasmodium; Mosquito; Animals; Malaria, Avian; Anopheles; New Zealand; Malaria; Mosquito Vectors; Culex; Plasmodium; Aedes; Birds; DNA, Protozoan